BUILDING GOOD MANNERS CHARACTER BASED ON ACEH CULTURE IN ISLAMIC PRIMARY EDUCATION INSTITUTIONS - Rita Sari; Farida Hanum; Muhammad Mauluddin Alif Utama (STAI Asy-Syukriyyah, 2024)
Character has been a serious issue that has been pursued for improvement since the 2003 curriculum until the independent curriculum. However, these efforts have not yet resulted in significant achievements. The purpose of writing this article is to describe efforts to penetrate Acehnese cultural values in learning to Madrasah Ibtidaiyah students so that they have a sense of pride in their own local culture. The researcher used a qualitative research type, with a literature study method. The results found that narit maja can be used as one of the sources to foster noble character values in Madrasah Ibtidaiyah. Of course, through a review of the theme or subject matter to match the narit maja to be given. Educational methods that can be used by teachers to strengthen noble moral character through narit maja are storytelling, exemplary, advice, habituation, reward, discussion, and the introduction of rules that must be agreed upon so as not to violate religious norms and general customs. The recommendation of this research is that narit maja can be included in the Aceh education curriculum, as local content. So that students are not unfamiliar with their own local culture.